Die Stimmen der Eroberten bei Ermoldus Nigellus. Eine Mahnung an Ludwig den Frommen und Pippin von Aquitanien - Foerster, Anne (Eroberte im Mittelalter: Umbruchssituationen erleben, bewältigen, gestalten)

To share or not to share: What risks would laypeople accept to give sensitive data to differentially-private NLP systems?

Privacy-Preserving Natural Language Processing - Habernal, Ivan; Mireshghallah, Fatemehsadat; Thaine, Patricia; Ghanavati, Sepideh; Feyisetan, Oluwaseyi (Proceedings of the 17th Conference of the European Chapter of the Association for Computational Linguistics: Tutorial Abstracts)

Trade-Offs Between Fairness and Privacy in Language Modeling - Matzken, Cleo; Eger, Steffen; Habernal, Ivan (Findings of the Association for Computational Linguistics: ACL 2023)

Crowdsourcing on Sensitive Data with Privacy-Preserving Text Rewriting - Mouhammad, Nina; Daxenberger, Johannes; Schiller, Benjamin; Habernal, Ivan (Proceedings of the 17th Linguistic Annotation Workshop (LAW-XVII))

Privacy-Preserving Models for Legal Natural Language Processing - Yin, Ying; Habernal, Ivan (Proceedings of the Natural Legal Language Processing Workshop 2022)

Text-Bild-Bezüge in illustrierten Flugblättern von 1500 bis 1700 - Wille, Manuel (Text und Bild: Relationen und Funktionen in Texten vom 8. bis 18. Jahrhundert : Akten zum internationalen Kongress 17. bis 19. Juni 2021)

An Optimized Third-Harmonic Injection Reduces DC-Link Voltage Ripple in Cascaded H-Bridge Converters up to 50% for all Power Factors - Unruh, Roland; Böcker, Joachim; Schafmeister, Frank (2023 25th European Conference on Power Electronics and Applications (EPE'23 ECCE Europe))
Star-connected cascaded H-bridge Converters require large DC-link capacitors to buffer the second-order harmonic voltage ripple. First, it is analytically proven that the DC-link voltage ripple is proportional to the apparent converter power and does not depend on the power factor for nominal operation with sinusoidal reference arm voltages and currents. A third-harmonic zero-sequence voltage injection with an optimal amplitude and phase angle transforms the 2nd harmonic to a 4th harmonic DC-link voltage ripple. This reduces the voltage ripple by exactly 50% for all power factors at steady-state at balanced conditions. However, this requires 54% additional modules for unity power factor operation and even 100% for pure reactive power operation to account for the increased reference arm voltages due to the large amplitude of the optimal third-harmonic injection. If not enough modules are available, an adaptive discontinuous PWM is utilized to still minimize the voltage ripple for the given number of modules and power factor. With a very limited number of modules (modulation index is 1.15), the proposed method still reduces the DC-link voltage ripple by 24.4% for unity power factor operation. It requires the same number of modules as the commonly utilized 3rd harmonic injection with 1/6 of the grid voltage amplitude and achieves superior results. Simulations of a 10 kV/1 MVA system confirm the analysis.
Keywords: Cascaded H-Bridge; Solid-State Transformer; Capacitor voltage ripple; Zero sequence voltage; Third harmonic injection

Fade-Over Strategy for use of Model Predictive Direct Self-Control with Field-Oriented Control - Pena, Mario; Meyer, Michael; Wallscheid, Oliver; Böcker, Joachim (2023 IEEE International Electric Machines and Drives Conference (IEMDC))

Review on: Christos Tsakas: Post-war Greco-German Relations, 1953-1981. Economic Development, Business Interests and European Integration, Basingstoke 2022. - Schönhärl, Korinna (Sehepunkte)

Plant-based dietary patterns and cardiometabolic risk factors in subgroups of individuals with diabetes - Weber, Katharina S.; Schlesinger, Sabrina; Lang, Alexander; Straßburger, Klaus; Maalmi, Haifa; Zaharia, Oana P.; Goletzke, Janina; Buyken, Anette; Trenkamp, Sandra; Wagner, Robert; Lieb, Wolfgang; Roden, Michael; et al. (Diabetologie und Stoffwechsel)

ABHÄNGEN - Ein- und Ausgrenzen, Kanonisieren, Kollaborieren in Pop, Kunst und Medien. - Jacke, Christoph (Impulse. Texte und Bilder zur Kunstvermittlung.)

Editorial. - Jacke, Christoph; Autsch, Sabine; Pickartz, Tim (Impulse. Texte und Bilder zur Kunstvermittlung.)

Zuweisung verteilter Speicher unter Maximierung der minimalen gewichteten Bandbreite - Decking, Leo
Bei dem betrachteten Speicherproblem werden Daten mit verschiedenen Zugriffswahrscheinlichkeiten auf Speicher mit verschiedenen Bandbreiten und Kapazitäten aufgeteilt, dabei sind Replikate erlaubt. Es wird die nach Zugriffswahrscheinlichkeit gewichtete kleinste Bandbreite der Daten maximiert. Wir zeigen, dass sowohl das diskrete Speicherproblem, bei dem die Bandbreite der Speicher jeweils gleichmäßig auf die dort abgelegten Daten aufgeteilt wird, als auch das kontinuierliche Speicherproblem, bei dem die Bandbreite der Speicher beliebig auf abgelegte Daten verteilt werden darf, NP-schwer ist. Es können also, wenn P ̸ = NP, keine effizienten Algorithmen für eine optimale Lösung existieren. Stattdessen zeigen wir jeweils einen 1/2-Approximationsalgorithmus.

On the Integration of Sampling Rate Synchronization and Acoustic Beamforming - Gburrek, Tobias; Schmalenstroeer, Joerg; Haeb-Umbach, Reinhold (European Signal Processing Conference (EUSIPCO))

Nietzsche’s Search for Philosophy: On the Middle Writings Keith Ansell-Pearson - Corall, Niklas (The Agonist)
In Nietzsche’s Search for Philosophy – On the Middle Writings, Keith Ansell Pearson directs his interpretive gaze to the middle writings of Nietzsche’s oeuvre, namely Human, All Too Human (HAH), Dawn and The Gay Science (GS). While at least in German Nietzsche scholarship, it is rather debatable whether or not the middle writings should have been considered “neglected”– with perhaps Dawn being a reasonable exception – it is important to read them as more than merely a detour from the “real Nietzsche” found in the Birth of Tragedy and then the late works. While Ansell-Pearson does not presume a homogeneous philosophical approach in the middle works, he characterizes the period as a whole and each work in itself as containing important aspects of Nietzsche’s “search for philosophy”, especially in consideration of Nietzsche’s attempts to “unify thought and life” (4) in what is labelled a “‘philosophical life’” (4).
Keywords: Ocean Engineering

Digitale Bruchstücke zwischen Faktalismus und Zukunftsnarration: Der Letzte Mensch und Algorithmische Regime - Corall, Niklas (Nietzsche, die Medien und die Künste im Zeitalter der Digitalisierung)

Digitizing Processes in Manufacturing Companies via Low-Code Software (to appear) - Weidmann, Nils; Kirchhoff, Jonas; Sauer, Stefan
Low-code development platforms (LCDPs) recently sparked interest in both academia and industry, promising to speed up software development and make it accessible to users with little or no programming experience. Thus, the mass-development of software applications that are custom-made to the tasks, skills, and preferences of end users is potentially enabled. Although different LCDPs have been analysed with respect to their functionality and applied to exemplary case studies in recent work, there is a shortage of experience reports in which LCDPs are used to digitize business processes in small and medium manufacturing enterprises. In this paper, we therefore summarize our experience from supporting industry partners to identify business processes that are suitable for being implemented with low-code technologies and to select an LCDP that meets the requirements of the business process while aligning with the overall digitization strategy of the respective company. We also present the opportunities and challenges of the low-code approach as perceived by industry partners. In summary, the low-code approach should be seen as an essential factor for the digitization of business processes in small and medium manufacturing companies.

Knowledge Transfer Concepts for Microgrids Sustainability - The Case of East Africa - Bogere, Paul; Temmen, Katrin; Bode, Henrik (2023 IEEE Global Engineering Education Conference (EDUCON))

Creativity in entrepreneurship: Dancing between nothing and structure - Hubner-Benz, Sylvia; Frese, Michael (Handbook of Organizational Creativity)

Scaffolding the human partner by contrastive guidance in an explanatory human-robot dialogue - Groß, A.; Singh, Amit; Banh, Ngoc Chi; Richter, B.; Scharlau, Ingrid; Rohlfing, Katharina J.; Wrede, B. (Frontiers in Robotics and AI)
Explanation has been identified as an important capability for AI-based systems, but research on systematic strategies for achieving understanding in interaction with such systems is still sparse. Negation is a linguistic strategy that is often used in explanations. It creates a contrast space between the affirmed and the negated item that enriches explaining processes with additional contextual information. While negation in human speech has been shown to lead to higher processing costs and worse task performance in terms of recall or action execution when used in isolation, it can decrease processing costs when used in context. So far, it has not been considered as a guiding strategy for explanations in human-robot interaction. We conducted an empirical study to investigate the use of negation as a guiding strategy in explanatory human-robot dialogue, in which a virtual robot explains tasks and possible actions to a human explainee to solve them in terms of gestures on a touchscreen. Our results show that negation vs. affirmation 1) increases processing costs measured as reaction time and 2) increases several aspects of task performance. While there was no significant effect of negation on the number of initially correctly executed gestures, we found a significantly lower number of attempts—measured as breaks in the finger movement data before the correct gesture was carried out—when being instructed through a negation. We further found that the gestures significantly resembled the presented prototype gesture more following an instruction with a negation as opposed to an affirmation. Also, the participants rated the benefit of contrastive vs. affirmative explanations significantly higher. Repeating the instructions decreased the effects of negation, yielding similar processing costs and task performance measures for negation and affirmation after several iterations. We discuss our results with respect to possible effects of negation on linguistic processing of explanations and limitations of our study.
Keywords: HRI; XAI; negation; understanding; explaining; touch interaction; gesture

Tod mit Kindern thematisieren - Magdeburg, Lena Maria (Grundschule)

Medienpädagogische Professionalisierung in der beruflichen Weiterbildung. Eine Studie aus Perspektive der biografischen Medienforschung - Dehmel, Lukas

A new approach to model the fluid dynamics in sandwich packings - Franke, Patrick; Shabanilemraski, Iman; Schubert, Markus; Hampel, Uwe; Kenig, Eugeny Y. (Chemical Product and Process Modeling)
Abstract Sandwich packings represent new separation column internals, with a potential to intensify mass transfer. They comprise two conventional structured packings with different specific geometrical surface areas. In this work, the complex fluid dynamics in sandwich packings is modeled using a novel approach based on a one-dimensional, steady momentum balance of the liquid and gas phases. The interactions between the three present phases (gas, liquid, and solid) are considered by closures incorporated into the momentum balance. The formulation of these closures is derived from two fluid-dynamic analogies for the film and froth flow patterns. The adjustable parameters in the closures are regressed for the film flow using dry pressure drop measurements and liquid hold-up data in trickle flow conditions. For the froth flow, the tuning parameters are fitted to overall pressure drop measurements and local liquid hold-up data acquired from ultra-fast X-ray tomography (UFXCT). The model predicts liquid hold-up and pressure drop data with an average relative deviation of 16.4 % and 19 %, respectively. Compared to previous fluid dynamic models for sandwich packings, the number of adjustable parameters could be reduced while maintaining comparable accuracy.
Keywords: Modeling and Simulation; General Chemical Engineering

When Did Europe Become Identified With Christianity? The Revolutionary Origins of an All Too Common Slogan - Süßmann, Johannes (Beyond Binaries. Religious Diversity in Europe)

Korpora für Deutsch als Fremdsprache – Potenziale und Perspektiven - Weber, Tassja; Flinz, Carolina; Mell, Ruth; Möhrs, Christine (Korpusgestützte Sprachanalyse. Grundlagen, Anwendungen und Analysen)

Novel Cascaded Incremental Nonlinear Dynamic Inversion Controller Approach for a Tiltrotor VTOL - Henkenjohann, Mark; Nolte, Udo; Henke, Christian; Trächtler, Ansgar (2023 International Conference on Unmanned Aircraft Systems (ICUAS))

Controlled Rivet Deformation During Self-piercing Riveting Through a Tailored Strength Distribution Within the Rivet Material - Uhe, Benedikt; Kuball, Clara-Maria; Merklein, Marion; Meschut, Gerson (Proceedings of the 14th International Conference on the Technology of Plasticity - Current Trends in the Technology of Plasticity.)

Assessing the Impact of the Powder Production Method on Ceramic-filled Polyamide Composites made by Laser Sintering - Kletetzka, Ivo; Neitzel, Fabian; Schmid, Hans-Joachim (Proceedings of the 34th Annual International Solid Freeform Fabrication Symposium)
Polymer composites represent the industry standard in injection molding for the production of plastic components with increased requirements in terms of heat resistance and stiffness. In the field of laser sintering (LS), these materials are less common so far. In order to extend the available material variety for the LS process, new ceramic-filled Polyamide 613 powders are investigated within the scope of this work. Here, the resulting properties from two different powder production methods are compared. One filled powder is produced by dry blending and the other powder with the same filler and filling ratio is produced by encapsulating the filler particles inside the polymer particles within the dissolution-precipitation process. It was found that encapsulating the filler particles can provide certain benefits for the processability, for example an improved powder flowability or better filler dispersion. However, encapsulating the filler also alters the thermal properties of the precipitated powder.

Intrinsic forming of hybrid parts made of laser-structured aluminium sheet and CFRP-Prepreg - Wu, Shuang; Freund, Jonathan; Delp, Alexander; Haubrich, Jan; Löbbecke, Miriam; Walther, Frank; Tröster, Thomas

Ibn Khaldûn and the Political Economy of Communication: A Reply to Graham Murdock - Fuchs, Christian (Critical Sociology)

Modellierung der axialen Dispersion in Struktur- und Anstaupackungen - Franke, Patrick; Shabanilemraski, Iman; Schubert, Markus; Hampel, Uwe; Kenig, Eugeny Y.

Autonomous Golf Putting with Data-Driven and Physics-Based Methods - Junker, Annika; Fittkau, Niklas; Timmermann, Julia; Trächtler, Ansgar (2022 Sixth IEEE International Conference on Robotic Computing (IRC))

Verfahren zum Betreiben einer elektrooptischen Übertragungsvorrichtung für beliebige Signale, Computerprogrammprodukt sowie Datenübertragungsvorrichtung - Kruse, Stephan; Scheytt, J. Christoph; Meinecke, Marc-Michael; Heiko Gustav, Kurz
Die Erfindung betrifft ein Verfahren zum Betreiben einer elektrooptischen Übertragungsvorrichtung, mit den Schritten: - Erzeugen eines optischen Trägersignals mittels einer optischen Signalquelle einer Basiseinrichtung der Übertragungsvorrichtung; - Erzeugen eines beliebigen Signals mittels der optischen Signalquelle; - Aufmodulieren des beliebigen Signals auf das optische Trägersignal in der Basiseinrichtung zu einem Übertragungssignal; - Übertragen des Übertragungssignals an eine Antenneneinrichtung der Übertragungsvorrichtung mittels eines optischen Übertragungsmediums; und - Trennen des beliebiges Signals und des Trägersignals in der Antenneneinrichtung. Ferner betrifft die Erfindung ein Computerprogrammprodukt sowie eine Übertragungsvorrichtung.

Einstellbare Signalquelle mit kleinem Phasenrauschen - Bahmanian, Meysam; Scheytt, J. Christoph
Die Erfindung betrifft eine einstellbare Signalquelle mit kleinem Phasenrauschen, aufweisend • einen optischen Mikrowellenphasendetektor (BOMPD) aufweisend • einen Intensitätsmodulator (BIM), mit einem optischen Signaleingang, einem Modulationseingang (I), und einem ersten Ausgang (O1) und einen zweiten Ausgang (O2), • eine erste Photodiode (PD1), die im Betrieb mit Licht des ersten Ausgangs (O1) bestrahlt werden kann, • eine zweite Photodiode (PD2), die im Betrieb mit Licht des zweiten Ausgangs (O2) bestahlt werden kann, • wobei die erste Photodiode (PD1) und die zweite Photodiode (PD2), im Betrieb vorgespannt in Reihe geschaltet sind, • wobei zwischen der ersten Photodiode (PD1) und der zweiten Photodiode (PD2) ein Abgriff für eine Abgriffs-Signal angeordnet ist, • weiterhin aufweisend eine steuerbare Gleichstromquelle, • wobei am Abgriff im Betrieb mittels der ersten Gleichstromquelle (N4) ein Offsetstrom einstellbar ist, womit die Symmetrie des optischen Mikrowellenphasendetektor im Betrieb durch einen Offsetstrom aufgehoben wird, • wobei der Abgriff mit einem eventuellen Offsetstrom an ein Tiefpassfilter geführt wird, • wobei das tiefpassgefilterte Abgriffs-Signal einem einstellbaren Oszillator (OSZ) zur Verfügung gestellt wird.

Softsensor model of phase transformation during flow forming of metastable austenitic steel AISI 304L - Rozo Vasquez, Julian; Arian, Bahman; Kersting, Lukas; Walther, Frank; Homberg, Werner; Trächtler, Ansgar

Hybrid Optimal Control for Dynamical Systems using Gaussian Process Regression and Unscented Transform* - Hesse, Michael; Timmermann, Julia; Trächtler, Ansgar (2023 European Control Conference (ECC))

Unterrichtsplanung mit sinnvoller Einbettung digitaler Medien im PU - Jordans, Melanie; Riese, Josef (Lernen, Lehren und Forschen in einer digital geprägten Welt. Gesellschaft für Didaktik der Chemie und Physik. Jahrestagung in Aachen 2022)

Case Study III: Challenges of lightweight design, vehicles, and rescuers - Akbulut Irmak, Emine Fulya; Hanses, Hendrik; Horwath, Ilona; Tröster, Thomas (Climate Protection, Resource Efficiency, and Sustainable Engineering)

Introduction to the Minitrack on Data-driven Services in Manufacturing: Innovation, Engineering, Transformation, and Management - Koldewey, Christian; Martin, Rabe; Dumitrescu, Roman; Winter, Johannes (Proceedings of the 56th Hawaii International Conference on System Sciences)

Datengestützte Produktplanung
Unter dem Einfluss der Digitalisierung wandeln sich mechatronische Produkte zunehmend in cyber-physische Systeme (CPS). Diese sind in der Lage, umfangreiche Daten während ihres Betriebs zu sammeln und über digitale Netzinfrastrukturen zur Verfügung zu stellen. Gemeinsam mit weiteren Daten aus der Betriebsphase versprechen sie wertvolle Erkenntnisse über das Produkt und dessen Nutzer, welche für die Hersteller der CPS insbesondere für die Planung zukünftiger Produktgenerationenrelevant sind. Die zielgerichtete Nutzung von Betriebsdaten in der strategischen Produktplanung stellt produzierende Unternehmen jedoch noch vor zahlreiche Herausforderungen, z. B. hinsichtlich der Identifizierung Erfolg versprechender Use Cases. Das vorliegende Buch greift diese Herausforderungen auf und stellt ein Instrumentarium vor, das produzierende Unternehmen zur datengestützten Produktplanung befähigt. Neben der Vorstellung praxiserprobter Methoden und Werkzeuge werden Einblicke in vier Pilotprojekte gegeben. Das Instrumentarium entstand im Forschungsprojekt „DizRuPt“, das vom Bundesministerium für Bildung und Forschung (BMBF) gefördert wurde.

Evaluation of the effects of different heating strategies on the joining partners during infrared welding of black polyamides - Schöppner, Volker; Gevers, Karina; Schraa, L.; Töws, P.; Uhlig, K.; Stommel, M.; Decker, J.

Evaluation of Infrared Welded Joints of Short Fiber Reinforced Thermoplastics Using Digital Image Correlation - Schöppner, Volker; Gevers, Karina; Schraa, L.; Uhlig, K.; Töws, P.; Decker, J.; Stommel, M. (Proceedings of the 2023 International Conference on Composite Materials)

Entwicklung von Scale-Up-Regeln für das quasisimultane Laserdurchstrahlschweißen (QSS) von Thermoplasten - Schöppner, Volker; Arndt, Theresa (Joining Plastics)

Dielectric Heating in the Vulcanization Process of Rubber Extrudates - Schöppner, Volker; Petzke, J.

Direktverschraubung additiv gefertigter Kunststoffbauteile - Moritzer, Elmar; Held, Christian

Conjunctive and additive group work reduce academic procrastination: insights from a vignette study - Koppenborg, Markus; Klingsieck, Katrin B.; Hüffmeier, Joachim (Current Psychology)
Abstract Group work can increase individual effort, performance, and positive affect, if group members perceive their own contribution as indispensable for the group product. A vignette methodology was applied to investigate whether group work may also reduce procrastination. The vignettes described a typical academic assignment, while varying the task structure (individual work vs. conjunctive group work vs. additive group work) and group member ability (high vs. low). For each vignette, student participants ( N = 443) provided ratings on their perceived indispensability, procrastination of the assignment, and affect. When group member ability was high, procrastination was lower in additive group work as compared to individual work. When group member ability was low, procrastination was lower in conjunctive group work as compared to both individual work and additive group work. As predicted, perceived indispensability mediated the difference in procrastination between conjunctive and additive group work. Moderation analyses further revealed that the effects were more pronounced for high trait procrastinators. Further, both types of group work led to increases in task-related positive affect as compared to individual work. By demonstrating the relevance of group work as a social factor, the results should be useful for the extension of existing programs targeting procrastination, and may inspire measures for preventing procrastination by changes in the study environment.
Keywords: General Psychology

GEProS - Entwicklung und Evaluation einer digitalen Simulation zur Förderung diagnostischer Kompetenz von Lehramtsstudierenden - Grotegut, Lea
Um Schüler*innenmerkmale korrekt zu beurteilen benötigen Lehrkräfte diagnostische Kompetenz. Insbesondere die genaue Einschätzung nicht-kognitiver Merkmale von Schüler*innen fällt Lehrkräften eher schwer. Dazu zählen auch mögliche Anzeichen für Lern- und Verhaltensauffälligkeiten. Maßnahmen zur Förderung diagnostischer Kompetenz fokussieren bisher größtenteils die Diagnostik fachspezifischer, situativer Urteilsgegenstände, wie Fehlkonzepte im Mathematikunterricht. Systematisch evaluierte Fördermaßnahmen, die das Erkennen und Beurteilen von Lern- und Verhaltensauffälligkeiten bei Schüler*innen fokussieren, existieren bisher nicht.Aus diesem Anlass wurde die digitale, problemorientierte Simulation GEProS zur Förderung diagnostischer Kompetenz von Lehramtsstudierenden entwickelt und systematisch in drei längsschnittlichen, (quasi-)experimentellen Kontrollgruppenstudien evaluiert. Die Ergebnisse zeigen, dass die GEProS einen Mehrwert für die Förderung diagnostischer Kompetenz insbesondere im Bereich selbstbestimmter Motivation bieten kann. Ein integriertes Quiz mit Feedback kann mittels testing effect darüber hinaus der Erwerb deklarativ-konzeptionellen Wissens als zentrale Disposition diagnostischer Kompetenz in GEProS unterstützen. Die Ergebnisse tragen durch das entwickelte Integrative Modell diagnostischer Kompetenz zur Theoriebildung sowie zur Forschung und Entwicklung im Bereich der Förderung diagnostischer Kompetenz bei, indem eine Maßnahme zur Förderung diagnostischer Kompetenz für einen fächerübergreifenden, zeitlich stabilen Urteilsgegenstand systematisch evaluiert wurde. Durch die Ableitung und Berücksichtigung wesentlicher Merkmale digitaler Simulationen trägt diese Arbeit außerdem zur theoretischen Fundierung digitaler Simulationen bei.

Kompetenzentwicklung in der Lehrkräftebildung: der Mehrwert einer digitalen Simulation - Grotegut, Lea; Klingsieck, Katrin B. (ZeHf – Zeitschrift für empirische Hochschulforschung)
Die Förderung diagnostischer Kompetenz in der Lehrer*innenbildung birgt zwei Herausforderungen: Erstens bleibt in großen Lehrveranstaltungen wenig Raum für die notwendige Anwendung theoretischen Wissens, zweitens können Fehlentscheidungen in realen diagnostischen Situationen gravierende negative Folgen für Schüler*innen haben. Eine digitale Simulation kann beiden Herausforderungen begegnen. In diesem Beitrag wurde eine digitale, problemorientierte Simulation zur Förderung diagnostischer Kompetenz von Lehramtsstudierenden evaluiert und mit einer textbasierten, problemorientierten und einer lehrendenzentrierten Kontrollgruppe verglichen. Die Ergebnisse zeigen positive Effekte für die digitale Simulation hinsichtlich der selbstbestimmten Motivation, aber einen geringeren Wissenszuwachs im Vergleich zum lehrendenzentrierten Setting. Die Selbstwirksamkeit nahm in allen drei Gruppen zu. Eine digitale Simulation bietet in der untersuchten Form somit einen, wenn auch geringen, Mehrwert für die Lehrkräftebildung im Bereich der Kompetenzentwicklung.
Keywords: General Earth and Planetary Sciences; General Engineering; General Environmental Science

Nächstes Jahr in Jerusalem – oder auch nicht. Perspektiven auf Deutschland und Israel in Olga Grjasnowas "Der Russe ist einer, der Birken liebt" und Mirna Funks "Winternähe" - Spener, Anna Maria (DINGS 2021. Beiträge zur Digitalen INternationalen Germanistischen Studierendentagung. Literatur des 20. und 21. Jahrhunderts)